Digest of the Laws of Pennsylvania, at 270, Hunting (1818) - (:unkn) unknown (General Publisher, 1760)
That no person whatsoever shall presume to shoot at or kill with a firearm any pigeon, dove, partridge, or other fowl in the open streets of the city of Philadelphia, or in the gardens, orchards and enclosures adjoining upon and belonging to any of the dwelling houses within the limits of the said city, upon the forfeiture of five shillings for every such offense.
--
Keywords: HUNTING REGULATION